Changes in life expectancy and life span equality during the COVID-19 epidemic in 2020-22 in Japan - Yuta Okada; Hiroshi Nishiura (PLoS ONE, 2026)
Objectives Life expectancy at birth is a demographic measure derived from age-specific mortality rates, reflecting the population’s mortality pattern and its changes over time. While life expectancy has been heavily applied to quantify the mortality impact of the COVID-19 pandemic, the present study not only decomposes the changes in life expectancy by age and cause of death but also assesses the shifts in the age pattern of mortality in Japan. With this aim, we first evaluated the relationship between life expectancy gap from 2020−21 and 2021−22 and indicators of COVID-19 epidemic size at prefectural level. We also conducted age- and cause-specific decomposition of life expectancy change. Trends of life span equality from 2000−22 were also evaluated at the national level. Prefectural analysis between 2021−22 life expectancy change and annual per-population COVID-19 cases, person days in intensive care, reported COVID-19 deaths did not reveal significant correlations, which was contrary to our analysis from 2020−21. However, decomposition analysis revealed substantial life expectancy shortening attributable to the over-35-year-old population, and large increases in death causes such as cardiovascular or respiratory disorders along with COVID-19. For the total population in Japan, life span equality, an inverse measure of the dispersion in ages at death (higher values indicate less variation), declined in 2020 but increased in 2021 and 2022 despite the shortening in life expectancy. There were several key findings in this work. First, the discrepancy between life expectancy change and COVID-19 statistics in 2022 may, among other factors, possibly be attributable to the growing ascertainment bias of COVID-19. Second, the increased contribution of cardiovascular disorders to life expectancy shortening is an alarming sign for the future. Third, Life span equality in 2021 and 2022 is likely attributed to increased mortality among the elderly.